Adomian decomposition method for solving two-dimensional Schrödinger equation - AL-Saif, A. (University of Thi-Qar Journal of Science, 2010)
In this paper, Adomian decomposition method is applied to approximate the solution oftwo-dimensional Schrödinger equation. Also, the convergence proof of the Adomiandecomposition method is presented. The method was compared with other methods in theaspects of convergence and accuracy. The results show that the Adomian decompositionmethod is more accurate, and has better convergence than the other methods in literature,and CPU times needed for this problem are reported.